2019
DOI: 10.9745/ghsp-d-19-00015
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences of mHealth Interactive Voice Messages Promoting Contraceptive Use After Menstrual Regulation in Bangladesh: Intimate Partner Violence Results From a Randomized Controlled Trial

Abstract: Automated interactive voice messages about post-menstrual regulation contraception delivered to women in Bangladesh via mobile phone were associated with increased reports of intimate partner violence. This finding highlights the importance of taking steps to minimize risk when delivering phone messages on sensitive topics and the need for assessing violence in such situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…These factors will differ between contexts. For example, the Reiss et al intervention in Bangladesh used voice messages 14 because participants in their formative research indicated that they felt voice messages were more private as they do not remain on the phone 34 . However, for some, voice messages may be more intrusive than text messages or other digital media because recipients have to answer the call to receive the message irrespective of where they are, what they are doing, or who they are with.…”
Section: Minimizing and Responding To Risks Of Harm In Srh Digital Inmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors will differ between contexts. For example, the Reiss et al intervention in Bangladesh used voice messages 14 because participants in their formative research indicated that they felt voice messages were more private as they do not remain on the phone 34 . However, for some, voice messages may be more intrusive than text messages or other digital media because recipients have to answer the call to receive the message irrespective of where they are, what they are doing, or who they are with.…”
Section: Minimizing and Responding To Risks Of Harm In Srh Digital Inmentioning
confidence: 99%
“…Improvements in knowledge and contraceptive or health-seeking behavior have been demonstrated 6 , 11 13 . However, not all studies show benefits, as exemplified by the Reiss et al intervention in Bangladesh that showed no effect on contraceptive use 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unintended effect appears to have been positive – and might be worth looking into developing as a way to help women access methods more comfortably. However, this highlights the need to check for unintended consequences not only of unintended harms of interventions [ 21 ] but also evaluations. A qualitative component that goes beyond ‘process evaluation’ to explore the context of the intervention from the point of view of the intended beneficiaries and other stakeholders has the potential to help with this.…”
Section: Discussionmentioning
confidence: 99%
“…A woman's younger age, low socioeconomic reputation and low academic attainment, low education of husband, dowry, perceived disobedience of wives, family conflict and children had recently been ill are the wide variety of individual risk elements for IPV in Bangladesh which was recognized by many research 22,23,26,27,34 .In Bangladesh, dowry is associated with violence seems to be less frequent in contrast with different South Asian settings 35,36 .A study has found an association between early marriage and IPV and stated that the incidence rate used to be modestly in villages which are (44.1%) with the reasonable occurrence of early child marriage (15-25%), and was the best (51.8%) in villages with the highest incidence of very early child marriage (>25 %) 31 .The lack of ability to work or to work properly, the incapability to furnish sexual satisfaction, and verbal conflict had been the major reason behind such abuse 37 .A study claimed that each physical and sexual IPV occurrence rate is greater amongst these respondents whose pregnancies were unintended and females belonging to the poorest category of relative family wealth 19 .Several studies showed that early reproductive women are more vulnerable to IPV who are in the range of 15-31 years 22,[25][26][27] .Muslim women are at greater risk of IPV in Bangladesh 32 .In addition, men who witnessed father-to-mother violence are more likely to perpetrate IPV, suggesting an intergenerational transmission of violence 38 .Moreover, ownership of jewellery/large household assets by woman, substance abuse by husband and his involvement in extramarital sex, and education of woman more than the husband increased the likelihood of IPV in Bangladesh 39 . A randomized controlled trial study reported that women who were allocated to receive interactive messages about contraception were more likely to report physical IPV compared with the control group receiving usual care 40 .In Bangladesh, junior men are at heightened risks of perpetrating IPV and thus reducing the perpetration of IPV by them men is very critical 41 .…”
Section: Risk Factors Of Ipv In Bangladeshmentioning
confidence: 99%